Controllable silk fibroin extracellular skeleton gel material for injection and preparation method thereof
Through physical crosslinking technology of silk fibroin, cellulose and hyaluronate, controllable extracellular skeleton gel materials were prepared, which solved the problem of uncontrollable crosslinking degree and molecular weight in the prior art, and realized the relationship with the human body The filling material that matches the skin microstructure, has good biocompatibility and mechanical properties, promotes tissue regeneration and degradation, and is suitable for filling in different skin parts.
Patent Information
- Application Number
- CN202411211191.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-02
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The existing medical beauty filling materials have problems such as uncontrollable crosslinking, uncontrollable molecular weight, insufficient biocompatibility, and easy absorption and swelling in injection tissue filling, making it difficult to effectively achieve controllable in-situ tissue regeneration, and commonly used chemical crossover There is a risk of cytotoxicity in the combination agent.
The extracellular skeleton gel material with silk fibroin as the main component is prepared by physical cross-linking technology, combining cellulose and hyaluronate to control the cross-linking degree and molecular weight of the gel, avoiding the use of chemical cross-linking agents, and designing A filler material that matches the microstructure of human skin, has good biocompatibility and mechanical properties.
The crosslinking degree and molecular weight are controlled, the degradation process matches the tissue regeneration process, reduces chemical crosslinking agent residues, improves biocompatibility and mechanical properties, promotes in-situ regeneration and degradation of tissues, and is suitable for different Filling requirements for skin areas.
Smart Images

Figure CN119215228A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a medical cosmetic filling material, and in particular to a controllable extracellular skeleton gel material for injection and a preparation method thereof. Background Art
[0002] There are many ways to regenerate tissues, such as intracellular / extracellular polymerization, in situ synthesis of functional polymers on living cells, or preparation of scaffolds in vitro and inoculation of cells for regeneration after implantation in vivo. However, these methods have great limitations. Intracellular / extracellular polymerization is an emerging field that is not yet mature. Functional polymers synthesized in situ by cells require complex means to achieve; and in vitro tissue engineering requires complex cell culture conditions to obtain in vitro functional tissues. Autocrine and paracrine signaling effects are difficult to reproduce in in vitro culture.
[0003] In situ tissue engineering is also an effective means of tissue engineering regeneration that combines the original regenerative capacity of tissues with engineered biomaterials. In this process, biomaterials provide a structural framework to promote the attachment and migration of host stem cells and progenitor cells, and promote the differentiation of these cells into specific cell types to achieve the purpose of repair or regeneration.
[0004] The ultimate goal of tissue regeneration is to use certain means to achieve cell migration and proliferation, remodel the extracellular matrix (ECM), and affect cell function, such as restructuring the cytoskeleton, activating integrins, and normal gene expression. ECM has a unique spatial organization, and the unique arrangement of cells and ECM can be observed in directional tissues such as muscles and nerves. In situ tissue engineering guides cell regeneration by designing a scaffold with a near-ECM structure, thereby creating an artificial ECM morphology, thereby achieving guided differentiation, cell encapsulation, in situ regeneration and protection, ECM remodeling, and tissue repair.
[0005] In the process of in situ tissue regeneration, the scaffold provided by the biomaterial should facilitate the penetration of cells and tissues after implantation, and then the scaffold should be decomposed and completely reabsorbed. The key point in this process is that the scaffold should need controlled degradation to guide in situ tissue regeneration. This process requires balancing the degradation rate of the scaffold and the regeneration rate of the tissue to complete the regeneration of structure and function.
[0006] The raw materials of in situ tissue engineering biomaterials are widely available. The materials need to be able to respond to biological signals and interact with the immune system and endogenous cells to stimulate regeneration. At the same time, the structure and biological properties need to be precisely controlled during the design process to guide endogenous cells to the site of injury. This technology has opened up unprecedented ways to customize the properties of biomacromolecules, achieve precise spatial control, and seamlessly integrate material biological entities.
[0007] Regenerated silk fibroin is highly favored for its excellent mechanical properties, excellent biocompatibility, biodegradability and multifunctional structure, and is widely used in the fields of biomedicine and tissue engineering. It has a unique protein spatial structure. The formation of a certain β-folding structure in regenerated silk fibroin can form nano-scale microfibrils, which overlap and aggregate to form a flocculent network structure. In the process of tissue regeneration, this property can be used to prepare scaffolds to simulate the structure of ECM, so as to achieve the purpose of cell proliferation and regeneration and remodeling of ECM.
[0008] In injectable tissue filling, implanting tissue engineering scaffolds to promote in situ tissue regeneration is an effective repair method. There are few products on the market that use this method for repair. Common products are pure physical fillers represented by hyaluronic acid, which have no regenerative effect and are prone to water absorption and swelling; the other type is microsphere products represented by poly-L-lactic acid and polycaprolactone, but their structure is loose and easily decomposed by the tissue environment and proteases, making it difficult to maintain long-term filling effects. These products are very different from the microstructure of human skin itself. In contrast, regenerated silk protein microfibers are good tissue regeneration filling materials due to their relatively dense and stable molecular structure and suitable degradation cycle. If the scaffold is prepared with this material as the base, and the scaffold is subjected to certain structural designs to simulate ECM, it can more effectively stimulate tissue regeneration.
[0009] In the existing inventions, silk fibroin and hyaluronate are cross-linked using chemical cross-linkers such as BDDE to form a composite gel material of a three-dimensional interpenetrating network of silk fibroin and hyaluronic acid. However, the degree of cross-linking is uncontrollable, and the use of chemical cross-linkers has certain cytotoxicity. After residual accumulation in the body, it is easy to cause risks such as redness, swelling, allergies, and cancer.
[0010] Therefore, it is a key research and development direction of silk fibroin tissue engineering materials to find a silk fibroin cell extracellular skeleton gel material with controllable crosslinking degree and molecular weight, a degradation process that matches the in situ tissue regeneration process, and a similar microstructure to human skin, and having good biocompatibility, water absorption, good mechanical properties and injectability. Different skin tissues have different corresponding tensions, and the rheological properties of the required filling materials are also different. The silk fibroin cell extracellular skeleton gel material for injection described in the present invention is adjusted through different processes to match different skin microstructures and the regeneration process of different skin positions, thereby achieving controllable in situ tissue regeneration.
[0011] The silk fibroin extracellular skeleton gel material for injection of the present invention achieves wrinkle removal and lifting effects by physical occupation in the early stage of being injected into the skin, without the phenomenon of volume expansion due to water absorption; in the later stage, under the extracellular skeleton-like structure of the gel, the gel material can promote the in situ regeneration of tissues, as manifested by the increase in the area proportion of collagen in pathological sections, and by adjusting the molecular weight and ratio of the components, the degradation rate of the gel material in the body can be controlled, as manifested by the retention rate of the gel in the body. Summary of the invention
[0012] In response to the above problems, the present invention intends to provide a silk fibroin extracellular skeleton gel material with controllable cross-linking degree and molecular weight, a degradation process that matches the in situ tissue regeneration process, and a microstructure similar to that of human skin, and has good biocompatibility, water absorption, good mechanical properties and injectability, and requires no use of chemical cross-linking agents to reduce corresponding residues.
[0013] The technical solution of the present invention is:
[0014] A silk fibroin extracellular skeleton gel for injection has controllable crosslinking degree and molecular weight, and its degradation process matches the in situ tissue regeneration process. It can be a controllable extracellular skeleton gel material for injection.
[0015] The gel comprises 5-50 parts of silk fibroin, 0.01-5 parts of cellulose, and 0.7-10 parts of hyaluronate, and the gel is prepared according to the following steps:
[0016] (1) Preparation of silk fibroin microfiber gel: adding cellulose to a silk fibroin aqueous solution to prepare a gel, crushing it, and sieving it to obtain a silk fibroin microfiber gel;
[0017] (2) Preparation of extracellular skeleton gel material: Hyaluronate is mixed with silk fibroin microfiber gel to make them physically cross-linked to form a silk fibroin extracellular skeleton gel material.
[0018] The gel material does not include any chemical cross-linking agents.
[0019] The cellulose is one or more of hydroxypropyl methylcellulose, hydroxypropyl cellulose, carboxymethyl cellulose, and hydroxyethyl cellulose, preferably hydroxypropyl methylcellulose. The hyaluronate is one or more of sodium hyaluronate, potassium hyaluronate, and magnesium hyaluronate in any proportion, preferably sodium hyaluronate.
[0020] Furthermore, the preparation method of the silk fibroin composite filler of the present invention is as follows: (1) Silk fibroin microfiber gel: put mulberry silk into a boiling sodium carbonate aqueous solution with a mass fraction of 0.1-5% or a mixed solution of sodium carbonate and sodium bicarbonate, heat and boil for 10-120 minutes, dry at 25-100°C, dissolve in a 9.3 mol / L lithium bromide aqueous solution, and bathe at 25-100°C for 10-120 minutes until the silk fibroin is fully dissolved, filter out insoluble particulate impurities with a 50-200 mesh filter bag, desalt and concentrate to obtain a silk fibroin aqueous solution with a specific molecular weight. After adding the cellulose solution to the silk fibroin solution with a mass concentration of 20%, ultrasonic treatment is performed by an ultrasonic crusher. After gelation, homogenize at 1500-24000rpm / min for 5min, sieve, and collect the silk fibroin microfiber gel that passes through a 200-325 mesh sieve; (2) Preparation of extracellular skeleton gel: Hyaluronic acid particles and silk fibroin microfibers are mixed, and allowed to stand at 25-60℃ for 2-8h to allow physical cross-linking, dialyze with dialysate, fill, and sterilize to form a silk fibroin extracellular skeleton gel material.
[0021] Furthermore, the degree of β-folding and the number of hydrogen bonds can be controlled through the static process + temperature control to control the cross-linking degree of the gel. The alkoxy group promotes the hydrophobic interaction between molecules, and the hydrogen bonds between the hydroxypropyl group and the water molecules in the hydroxypropyl methylcellulose delay the formation of the gel. Under the hydrophobic interaction of cellulose, the β-folding structure is evenly distributed, the cross-linking density is higher, and its cross-linking form is similar to the extracellular skeleton.
[0022] Furthermore, the extracellular skeleton gel is composed of the following raw materials in the following mass ratio: 5-50 parts of silk fibroin, 0.01-5 parts of cellulose, and 0.7-10 parts of hyaluronate, preferably 10-50 parts of silk fibroin, 0.01-5 parts of cellulose, and 0.7-5 parts of hyaluronate.
[0023] It is further preferred that the ratio of silk fibroin to hyaluronate is greater than or equal to 2:1, 3:1 or 4:1.
[0024] In addition, it is preferred that the ratio of silk fibroin to hyaluronate is greater than or equal to 1.5:1, or less than or equal to 1.618:1, or 1.5≤silk fibroin / hyaluronate≤1.618.
[0025] Furthermore, in step (1), the molecular weight of the silk fibroin is between 50 kDa and 350 kDa.
[0026] Furthermore, the molecular weight of the cross-linked hyaluronic acid particles in step (2) is between 500 kDa and 2400 kDa, preferably between 1500 kDa and 2400 kDa.
[0027] Furthermore, in step (2), after the silk fibroin microfiber gel and the hyaluronic acid particles are mixed evenly, the mixture is preferably allowed to stand at 40-55°C.
[0028] Furthermore, in step (2), after the silk fibroin microfiber gel and the hyaluronic acid particles are mixed evenly, the mixture is preferably allowed to stand for 4 to 6 hours.
[0029] The present invention provides the silk fibroin extracellular skeleton gel material, which has the advantages of controllable size, high molecular weight, controllable cross-linking degree, easy filling, high affinity to the skin, etc., and is more suitable as a soft tissue filling material than conventional silk fibroin fillers. The tension and strength of different skin parts are different, corresponding to different rheological properties of the material, i.e., elastic modulus and viscous modulus. The alkoxy group promotes the intermolecular hydrophobic interaction and induces the blending system (mixed solution) to undergo phase separation through the nucleation-growth mechanism. Phase separation leads to the generation of SF-enriched phase, increases the local concentration of SF, and promotes the transformation of SF molecules from random coil / helical structure to β-folded structure. This process is somewhat similar to the "macromolecular crowding effect" in protein folding. The β-folded structure formed between SF molecules acts as a physical cross-linking point in the gel network. As the phase separation proceeds, the phase structure becomes coarser. At the same time, the β-folded structure formed between SF molecular chains gradually increases until a gel network that runs through the system is formed. The β-folded structure formed between SF molecular chains is further increased and improved, providing more cross-linking points, allowing the gel network to develop, while the movement of molecular chains in the dispersed phase is restricted, and some molecular chains are even severely restricted. The formed phase structure is "frozen" and gel is formed.
[0030] In addition, when the hydrogen bonds between the hydroxypropyl group and the water molecules in cellulose, such as hypromellose, delay the formation of gel, the internal structure of the gel is formed slowly and uniformly. Therefore, the macroscopic mechanical properties of the gel are stronger. By regulating the β-folding speed and ratio of silk fibroin at different temperatures, the degree of physical crosslinking of the gel material of the present invention is adjusted.
[0031] The soft tissue filling material refers to micro-plastic surgery filling materials such as facial wrinkle removal.
[0032] Beneficial effects of the present invention
[0033] (1) The raw material of the hydrogel of the present invention is low-cost silk fibroin certified by the U.S. Food and Drug Administration (FDA), so the obtained hydrogel has good biocompatibility and biodegradability.
[0034] (2) The mechanical strength of the hydrogel of the present invention is controllable. It can be seen from the elastic modulus and viscous modulus that a series of hydrogels with different mechanical strengths can be prepared simply by changing the molecular weight and ratio, thereby meeting the usage requirements of different facial skins.
[0035] (3) The hydrogel of the present invention is similar to the extracellular skeleton in terms of structure, size and function. The components are all fibrous proteins with a diameter of 5-30 nm. They play an important role in maintaining the normal morphology of cells, bearing certain external forces, and maintaining the normal operation of various cell functions. The mechanical properties are comparable to those of natural facial skin tissue. The extracellular skeleton also plays an important role in the transportation and transport of substances. The hydrogel of the present invention can also promote the migration and differentiation of surrounding fibroblasts (see Figure 3 ), achieving tissue regeneration.
[0036] (4) The preparation method of the hydrogel of the present invention is green, environmentally friendly, low-cost, easy to implement, and is expected to be used for large-scale commercial production. The silk protein nanofiber hydrogel of the present invention can be widely used in biomedical materials and nano-functional materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The SEM, TEM and AFM images of the silk fibroin extracellular skeleton gel disclosed in Example 1 of the present application, and the AFM images of four types of silk fibroin microfibers with different molecular weights;
[0038] Figure 2 Schematic diagram of the cross-linking between silk fibroin microfibril gel and cellulose;
[0039] Figure 3 The in vivo retention rate of the samples and comparative examples in Example 3-2 after subcutaneous implantation at different times;
[0040] Figure 4 Comparison of inflammatory responses in mice of Example 3-2 and the control group 2 weeks after implantation;
[0041] Figure 5 The collagen production rate promoted by the samples and the comparative examples in Example 3-2 at different times of subcutaneous implantation; the larger the collagen area ratio, the stronger the product's ability to stimulate skin tissue regeneration.
[0042] Figure 6 Schematic diagram comparing the ability of the samples in Example 3-2 and the comparative example in promoting collagen regeneration during implantation experiments. DETAILED DESCRIPTION
[0043] The present disclosure generally relates to soft tissue fillers, such as skin fillers and subcutaneous fillers, based on silk fibroin, cellulose, hyaluronic acid (HA) and pharmaceutically acceptable salts of HA (such as sodium hyaluronate). The silk fibroin-based composition of the present invention has enhanced stability, the extracellular skeleton gel material is similar to the structure of the extracellular matrix (ECM) in the human body, and after implantation, cells can synthesize and deposit new proteins on the surface of the biomaterial to reshape the part of the ECM, and its degradation process matches the tissue regeneration process, thereby achieving in situ regeneration of the tissue.
[0044] The stable composition maintains at least one or all of the following aspects after effective autoclaving and / or long-term storage: translucent to milky gel, suitable pH value, extrusion force and / or rheological characteristics, silk fibroin concentration, HA concentration, sterility and molar osmotic pressure concentration. Also provided are methods or processes for preparing such silk fibroin-based compositions and products prepared by these methods or processes.
[0045] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0046] Example 1: Controllable silk fibroin extracellular skeleton gels using silk fibroin of different molecular weights
[0047] Silk fibroin microfiber gel: The mulberry silk was degummed, dissolved, desalted and concentrated, and the pore size systems of 50kDa-100kDa, 100kDa-150 kDa, 150 kDa-200 kDa, and 200 kDa-350 kDa were selected respectively to prepare regenerated silk fibroin solutions with molecular weights of 50kDa-100kDa, 100kDa-150 kDa, 150 kDa-200 kDa, and 200 kDa-350 kDa, and the mass concentrations were all 20%.
[0048] Prepare a 5% hydroxypropyl methylcellulose solution, take 1 ml, add it to 125 ml of the above silk fibroin aqueous solution, so that the silk fibroin is 5 parts and the cellulose is 0.01 parts, and mix it for 1 minute under the condition of 3000rpm / min in a vortex mixer. Ultrasonic treatment is carried out by ultrasonic crusher, with an amplitude of 75%, intermittent ultrasonication (ultrasonication 50s, stop 10s), and ultrasonication for a total of 5 minutes.
[0049] Then, the mixture was allowed to stand at 90° C. to form a gel, and was homogenized at 24000 rpm / min for 5 min. The mixture was sieved to collect the silk fibroin microfiber gel passing through a 200-mesh sieve.
[0050] Preparation of extracellular skeleton gel material: 2.5 parts of sodium hyaluronate particles with a molecular weight of 1000 kDa-1500 kDa were prepared in triplicate and mixed with the silk fibroin microfiber gel prepared in step 1. Subsequently, cross-linking was performed at 55° C. for 6 hours.
[0051] The dialysis was performed under magnetic stirring using PBS buffer with a pH value of 7.4 as the dialysis fluid, and the dialysis fluid was replaced every 2 hours for about 72 hours.
[0052] The dialyzed gel was filled and sterilized by high pressure. The obtained silk fibroin extracellular skeleton gels were recorded as samples 1-1, 1-2, 1-3, and 1-4 respectively.
[0053] Table 1 shows the rheological data of controllable silk fibroin extracellular skeleton gels prepared from silk fibroin with different molecular weights.
[0054] Table 1 Rheological data of extracellular skeleton gels of silk fibroin with different molecular weights
[0055]
[0056] As the molecular weight increases, the elastic modulus and viscous modulus of the gel formed increase significantly. Silk fibroin microfiber gels with different molecular weights can be selected according to the usage. As the molecular weight increases, the elastic modulus and viscous modulus of the gel formed increase significantly. Silk fibroin microfiber gels with different molecular weights can be selected according to the usage. Figure 1 The following are the SEM, TEM and AFM images of the silk fibroin extracellular skeleton gel prepared in the embodiment, and the AFM images of four different molecular weight silk fibroin microfibers. The results show that the SF gel is composed of a nano-microfiber network, the length of the nano-microfiber is about several hundred nanometers, and the width is about 5nm. Due to the obvious entanglement and bifurcation between the microfibers, a gel visible to the naked eye can be formed. It can be seen from the AFM images of microfibers with different molecular weights that the crosslinking degree of the gel can be effectively controlled according to the different molecular weights of the silk fibroin, such as Figure 2 shown.
[0057] Depending on the degree of cross-linking of the gel, its degradation effect in the tissue is different, so the controllability of gel degradation can be achieved.
[0058] Example 2: Selecting controllable silk fibroin extracellular skeleton gels with different molecular weights of sodium hyaluronate
[0059] Silk fibroin microfiber gel: degumming, dissolving, desalting and concentrating mulberry silk, selecting a system with a pore size cutoff of 50-150 kDa, and preparing a regenerated silk fibroin solution with a molecular weight of 50~150 kDa and a mass concentration of 20%.
[0060] Prepare a solution of hydroxypropyl methylcellulose, add it to the aforementioned silk protein aqueous solution, and mix it for 1 minute at 3000 rpm / min in a vortex mixer. Ultrasonicate it with an ultrasonic crusher, with an amplitude of 80%, intermittent ultrasonication (ultrasonication for 50 seconds, stop for 10 seconds), and ultrasonication for a total of 5 minutes.
[0061] Then, the mixture was allowed to stand at -20°C to form a gel, homogenized at 20,000 rpm / min for 5 min, and sieved. The silk fibroin microfiber gel that passed through a 325-mesh sieve was collected to prepare 4 portions.
[0062] Preparation of extracellular skeleton gel material: Sodium hyaluronate particles with molecular weights of 500kDa-1000kD; 1000kDa-1500kD; 1500kDa-2000kD; 2000kDa-2400kDa were mixed with the silk fibroin microfiber gel in step 1, respectively, so that the ratio of silk fibroin: cellulose: hyaluronic acid was 15:2:5. Then, cross-linking was performed at 25°C for 12 hours.
[0063] Phosphate buffer with a pH of 7.4 was used as the dialysate, and the dialysate was replaced every 2 hours under magnetic stirring for about 72 hours.
[0064] The dialyzed gel was filled and sterilized under high pressure. The samples were named 2-1, 2-2, 2-3, and 2-4 respectively.
[0065] In Example 2, the rheological data of controllable silk fibroin extracellular skeleton gel prepared by hyaluronic acid with different molecular weights are shown in Table 2 below, among which 2-4 has a slightly higher elastic modulus, so the molecular weight of hyaluronic acid is preferably 1500 kDa-2400 kDa.
[0066] Table 2 Rheological data of controllable silk fibroin extracellular skeleton gels prepared by hyaluronic acid with different molecular weights
[0067]
[0068] Example 3: Controllable silk fibroin extracellular skeleton gels of different types of cellulose
[0069] Silk fibroin microfiber: 40g of mulberry silk was degummed, dissolved, desalted and concentrated, and a system with a cutoff pore size of 50kDa-150kDa was selected to prepare a regenerated silk fibroin solution with a molecular weight of 50-150kDa and a mass concentration of 20%.
[0070] A 5% hydroxypropyl cellulose solution was prepared and added to the aforementioned silk fibroin aqueous solution, and mixed for 1 min at 3000 rpm / min using a vortex mixer. The solution was then ultrasonicated using an ultrasonicator with an amplitude of 70% and intermittent ultrasonication (50 s ultrasonication and 10 s rest) for a total of 5 min.
[0071] Prepare a 5% hydroxypropyl methylcellulose solution, add it to the aforementioned silk fibroin aqueous solution, and mix it for 1 min at 3000 rpm / min on a vortex mixer. Ultrasonicate it with an ultrasonic crusher, with an amplitude of 70%, intermittent ultrasonication (ultrasonication for 50 s, rest for 10 s), and ultrasonication for a total of 5 min.
[0072] A 5% carboxymethyl cellulose solution was prepared and added to the aforementioned silk fibroin aqueous solution, and mixed for 1 min at 3000 rpm / min using a vortex mixer. Ultrasonic treatment was performed using an ultrasonic crusher with an amplitude of 70% and intermittent ultrasonication (ultrasonication for 50 s, rest for 10 s) for a total of 5 min.
[0073] Then, the mixture was allowed to stand at -20°C to form a gel, homogenized at 28000 rpm / min for 5 min, and sieved to collect the silk fibroin microfiber gel that passed through a 300-mesh sieve.
[0074] Preparation of extracellular skeleton gel material: prepare sodium hyaluronate particles with a molecular weight of 1500 kDa-2000 kDa, and mix them with the silk fibroin microfiber gel in step 1. Make the ratio of silk fibroin: cellulose: hyaluronic acid 4:1:1. Then, cross-link at 47°C for 2 hours.
[0075] The dialysis was performed under magnetic stirring using PBS buffer with a pH value of 7.4 as the dialysis fluid, and the dialysis fluid was replaced every 2 hours for about 72 hours.
[0076] The dialyzed gel was filled and sterilized under high pressure, and recorded as samples 3-1, 3-2, and 3-3.
[0077] Table 3 Test data of silk fibroin extracellular skeleton gel material with different types of cellulose added
[0078]
[0079] At the same concentration, the gel uniformity of hydroxypropyl cellulose is very poor, with large chunks of gel and a small amount of water mixed in the system. The gel uniformity of hydroxypropyl methylcellulose is very good, and its elastic modulus is suitable for soft tissue filling. The gel formed by carboxymethyl cellulose has a lot of precipitation and is not completely gelled, with a large amount of precipitation produced.
[0080] Example 4: Controllable silk fibroin extracellular skeleton gel
[0081] Under the conditions of Example 3, samples with different proportions were prepared and their rheological properties were tested;
[0082] Sample 4-1: 10 parts of silk fibroin, 1.25 parts of cellulose, and 5 parts of sodium hyaluronate;
[0083] Sample 4-2: 10 parts of silk fibroin, 1.88 parts of cellulose, and 5 parts of sodium hyaluronate;
[0084] Sample 4-3: 20 parts of silk fibroin, 2.5 parts of cellulose, and 4 parts of sodium hyaluronate;
[0085] Sample 4-4: 15 parts of silk fibroin, 1.25 parts of cellulose, and 5 parts of sodium hyaluronate;
[0086] Sample 4-5: 15 parts of silk fibroin, 1.88 parts of cellulose, and 5 parts of sodium hyaluronate;
[0087] Sample 4-6: 20 parts of silk fibroin, 1.25 parts of cellulose, and 5 parts of sodium hyaluronate;
[0088] Rheological data test method: The rheometer was used at (25±0.2)℃, with a 25mm rotor, a plate gap of 1mm, and a fixed deformation of 0.5%. The shear rate was scanned from 0.01 Hz to 100 Hz.
[0089] The elastic modulus and viscous modulus of the material are obtained at 1 Hz (simulating skin tissue tension).
[0090] Table 4 Rheological data of controllable silk fibroin extracellular skeleton gel prepared with different component ratios
[0091]
[0092] By controlling the variables of the number of each component and analyzing the influence of each component on the mechanical properties of the material, the increase in the concentration of each component will increase the elastic modulus of the material. Among them, the concentration of silk fibroin has the greatest influence on the mechanical properties of the material and is decisive; in the gelation mechanism we proposed, the β-folded structure formed between silk fibroin molecules plays a key role in the formation of the gel network. This explains the law that the gel modulus is positively correlated with the silk fibroin content found in rheological experiments. Simply put, the microfibers formed by the gradual increase of the β-folded structure formed between the silk fibroin molecular chains are the key to the composition of the gel and the gel network throughout the system. When the concentration of silk fibroin is higher, the more fibers there are, the denser the gel network is, and the higher the elastic modulus is.
[0093] Embodiment 5:
[0094] Preparation of silk fibroin microfibers: Select a system with a 50kDa-150kDa cutoff pore size, prepare a regenerated silk fibroin solution with a molecular weight of 50-150kDa, and ultrasonically treat to obtain sample 5-1. Prepare 5 ml of 5% hydroxypropyl methylcellulose solution, add it to 12.5 ml of the aforementioned silk fibroin aqueous solution, and mix it for 1 min under a vortex mixer at 3000rpm / min. Ultrasonic treatment was performed using an ultrasonic crusher with an amplitude of 70%, intermittent ultrasound (ultrasonication for 50s, stop for 10s), and ultrasound for a total of 5min to obtain sample 5-2. Sample 5-3 was obtained in the manner of Example 3. And on the basis of sample 5-1, 0.60 g of sodium hyaluronate particles with a molecular weight of 1500kDa-2000kDa were added and mixed to form sample 5-4.
[0095] Table 5 Modulus test results of samples of four different components
[0096]
[0097] The modulus test was performed on the four samples, and the results of the modulus test are shown in Table 4 below. The test results show that in sample 5-4, when only hyaluronic acid is added to the silk fibroin microfibers, the modulus is slightly increased. It can also be found in macroscopic observation that sample 5-4 cannot form a gel scaffold under the naked eye. The modulus result of sample 5-2 proves that the intermolecular hydrophobic interaction of cellulose in the silk fibroin microfibers causes a significant increase in the modulus. It can be found in sample 5-3 that after the physical cross-linking process after the addition of the three components, the sample obtains a high modulus, proving that it has obtained a stable gel structure.
[0098] Comparative Example (CN102836465B):
[0099] (1) Preparation of silk fibroin microspheres: Mulberry silk was degummed, dissolved, desalted and concentrated, and purified water was used to prepare a 5% silk fibroin solution.
[0100] At 25°C, the 5% silk fibroin solution was allowed to stand to form 5 g of white gel material. The gel material was homogenized with a homogenizer at 24000 rpm / min for 5 min to obtain 5 g of silk fibroin gel particles of different diameters. After filtration, 3.5 g of silk fibroin particles passed through a 200-mesh sieve were collected. A small amount of the collected silk fibroin particles were weighed and dried to constant weight to determine the water content of the silk fibroin particles, and the mass concentration of the silk fibroin particles was determined to be 3.23%.
[0101] (2) Silk fibroin hyaluronic acid composite gel: 0.7 g of sodium hyaluronate was dissolved in 7 ml of 1% sodium hydroxide solution to prepare a 0.1 g / ml sodium hyaluronate solution, and 0.712 g of silk fibroin particles obtained in step (1) (0.023 / 0.0323=0.712 g, the dry weight of silk fibroin particles is 0.023 g) was added to the sodium hyaluronate solution. After thorough mixing, 56 μl (0.056 g) of BDDE (1,4-butanediol diglycidyl ether) was added. After mixing evenly, the mixture was placed at 40°C for 4 hours for cross-linking to form a silk fibroin-HA composite gel material.
[0102] The silk fibroin-HA composite gel material was added to a dialysis bag of MW 8,000-14,000, and PBS buffer with a pH value of 7.4 and a temperature of 37°C was used as the dialysate, and the dialysis treatment was performed under magnetic stirring. The composite gel material after the dialysis treatment was homogenized by a homogenizer at 24,000 rpm / min for 10 minutes, and then placed in a syringe for squeezing to make the gel pass through a 60-mesh sieve, and the composite gel particles were collected, sterilized with high-temperature and high-pressure steam at 120°C for 15 minutes, and then aseptically packaged and loaded into a disposable syringe. Thus, 35 g of silk fibroin hyaluronic acid composite gel for injection was obtained, which can be used as a subcutaneous injection product.
[0103] The test method of the crosslinking agent is: take the same amount of the sample of Example 3-2 and the comparative sample and put them into a dialysis bag, then soak them in PBS, and take the solution outside the dialysis bag as the test solution at 2 weeks, 4 weeks, and 8 weeks. The residual amount of BDDE is tested by gas chromatography, and the specific test method is:
[0104] 1) Instruments and reagents: gas chromatograph, FID detector, DB-17 chromatographic column (30 mX0.32 mm, film thickness 0.50 μm), 1,4-butanediol diglycidyl ether standard, acetone.
[0105] 2) Chromatographic conditions
[0106] Chromatographic column: DB-17 (0.32 mm x 30 m, film thickness 0.50 μm)
[0107] Column temperature: initial temperature 150℃, increase to 260℃ at 30℃ / min, and maintain for 10 min.
[0108] Detector: FID.
[0109] Carrier gas: N2.
[0110] Inlet temperature: 260°C.
[0111] Detector temperature: 300°C.
[0112] Carrier gas flow rate: 5 mL / min.
[0113] 3) Sample pretreatment: accurately weigh the solution to be tested, place it in a 10 mL volumetric flask, add an appropriate amount of acetone, shake and dilute to the scale, shake well, filter, and take the filtrate.
[0114] 4) Sample test: Accurately measure 1 μl of the test solution and the reference solution respectively, inject them into the gas chromatograph, record the chromatogram, and calculate the peak area according to the external standard method.
[0115] Table 6 Crosslinking agent residue data of Example 3-2 and Comparative Example
[0116]
[0117] From the cross-linking residual data, it can be seen that since the present invention is physically cross-linked and does not contain any cross-linking agent, no cross-linking agent remains at any time. In the comparative example, due to the addition of a cross-linking agent, as the hyaluronic acid degrades, the chemical cross-linking agent gradually precipitates, which may cause an inflammatory reaction in the tissue and be harmful to the tissue. Figure 3 It can also be found that the inflammatory response of the comparative example is higher than that of the example.
[0118] Application examples:
[0119] The gels obtained in Example 3-2 and the comparative example were implanted subcutaneously in mice, and pathological sections were prepared after a certain period of time. The inflammatory response of the implanted materials was observed by HE staining, and the promotion of collagen regeneration was observed by immunohistochemical staining.
[0120] Table 7 Histopathological evaluation criteria for characterizing inflammatory response after material implantation
[0121]
[0122] After the material is implanted in the body, the inflammatory reaction is most intense and obvious about 2 weeks. Figure 5 The inflammatory response of Example 3-2 and the control mice 2 weeks after implantation is shown. The dark dots in the figure are lymphocyte nuclei. It can be seen that there are a large number of lymphocytes infiltrating around the control implant, and the inflammatory score is high. There are only a few lymphocytes around Example 3-2, and the inflammatory response is small. The biocompatibility of the gel of the present invention is better than that of the control.
[0123] Comparison of inflammatory response in the implantation experiment of Example 3-2 and the comparative mouse experiment is shown in Figure 4 , is the rate of promoting collagen production of the samples and the comparative examples implanted subcutaneously at different times in Example 3-2. Figure 5 , the schematic diagram comparing the ability of the sample in Example 3-2 and the comparative example to promote collagen regeneration in the implantation experiment is shown in Figure 6As can be seen from the figure below, after the Example 3-2 was implanted in mice, the inflammatory response was lower than that of the control group, while the collagen production capacity was higher than that of the control group. The evidence of its production capacity can be seen in the immunohistochemistry comparison diagram. It can be seen that the silk fibroin extracellular skeleton gel material claimed in the present invention has a structure similar to that of ECM, and its tissue in situ growth capacity is higher than that of the control group, and it will not produce a high inflammatory response, and has good biocompatibility.
[0124] Specifically: Figure 3 The in vivo retention rate of the samples and the comparative examples in Example 3-2 after subcutaneous implantation at different times
[0125] In the initial stage of implantation, the hyaluronic acid in the comparative product absorbs water and swells, while the hydrogel described in the present invention does not absorb water and swells, maintaining the initial volume, and the clinical manifestation is that the facial injection site does not become "steamed"; as the implantation time increases, the comparative product degrades quickly, while the hydrogel described in the present invention has a stable degradation rate.
[0126] Figure 4 The inflammatory response of Example 3-2 and the control mice was compared 2 weeks after implantation in the body. After Example 3-2 was implanted in the mice, the inflammatory response was lower than that of the control, proving that the silk fibroin extracellular skeleton gel material has good biocompatibility, a structure similar to that of ECM, and does not produce a high inflammatory response.
[0127] Figure 5 The collagen production rate promoted by the samples and the comparative examples in Example 3-2 at different times of subcutaneous implantation; the larger the collagen area ratio, the stronger the product's ability to stimulate skin tissue regeneration.
[0128] Figure 6 Schematic diagram comparing the ability of the sample in Example 3-2 and the comparative example to promote collagen regeneration in a 14-week implantation experiment.
[0129] Immunohistochemical staining was performed on the pathological sections to analyze the material's ability to promote collagen regeneration. The darker the staining and the larger the area, the higher the proportion of collagen and the better the regeneration effect of the material. Before the material is completely degraded, as the implantation time increases, the more collagen secretion is promoted. Figure 6 The samples in Example 3-2 and the control group were implanted in mice for 14 weeks, and the sections were immunohistochemically stained. The tissue staining in Example 3-2 was obviously darker and larger in area, so the regeneration ability of the sample in Example 3-2 was stronger than that in the control group.
[0130] Example 6: Controllable silk fibroin extracellular skeleton gel
[0131] Under the conditions of Example 3, samples with different ratios were prepared, the porosity of each sample was measured by liquid replacement method, and cell co-culture was performed to observe the adhesion and proliferation of cells on the material.
[0132] Sample 6-1: 13 parts of silk fibroin, 2.5 parts of cellulose, and 10 parts of sodium hyaluronate;
[0133] Sample 6-2: 15 parts of silk fibroin, 2.5 parts of cellulose, and 10 parts of sodium hyaluronate;
[0134] Sample 6-3: 16.18 parts of silk fibroin, 2.5 parts of cellulose, and 10 parts of sodium hyaluronate;
[0135] Sample 6-4: 18 parts of silk fibroin, 2.5 parts of cellulose, and 10 parts of sodium hyaluronate.
[0136] The three-dimensional structure inside the gel, including pore size and porosity, can regulate cell behavior. Appropriate porosity is required for cell adhesion and proliferation. When the product ratio changes, since microfibers are the key to the composition of the gel, when the silk protein content increases, samples 6-2 and 6-3 have greater porosity. The proliferation of cells on the material can also prove that samples 6-2 and 6-3 have higher cell proliferation rates than 6-1 and 6-4, providing more adhesion sites and a microenvironment suitable for survival, that is, the effect of preparing silk protein extracellular skeleton gel is better when 1.5≤silk protein / hyaluronate≤1.618 is met.
[0137] Porosity data testing method: Place the freeze-dried gel scaffold into a n-hexane solvent with a volume of V1, and allow the n-hexane to fully fill the pore structure of the scaffold under a certain negative pressure. The solvent volume at this time is recorded as V2. Then take out the scaffold filled with n-hexane, and record the solvent volume at this time as V3. The porosity (Porosity) calculation formula of the porous scaffold is: Porosity (%) = [(V1 − V3) ⁄ (V2 − V3)] × 100%.
[0138] Cell proliferation rate: L929 cells were cultured in 96-well plates. After 3-5 days of culture, MTT solution was added to each well for treatment. The absorbance value was measured on an enzyme-linked immunosorbent assay (ELISA) at a wavelength of 490 nm. Cell proliferation rate = (absorbance value of the experimental group - absorbance value of the blank control) / (absorbance value of the control group - absorbance value of the blank control) × 100%.
[0139] Table 8 Data on the porosity and cell proliferation rate of controllable silk fibroin extracellular skeleton gels prepared with different component ratios
[0140]
[0141] By controlling the silk fibroin and hyaluronate fraction variables, the influence on the internal pores of the gel is analyzed. Suitable pore size is necessary for tissue formation, to promote the diffusion of nutrients, oxygen and waste between cells. The hydrogel network of appropriate proportion is stable, has suitable pore size and porosity, is conducive to the adhesion and growth of cells on the surface. By the experiment in embodiment 6, it is found that when meeting 1.5≤silk fibroin / hyaluronate≤1.618, the silk fibroin extracellular skeleton gel with good porosity and cell proliferation rate can be obtained.
Claims
1. A controllable silk fibroin extracellular skeleton gel material for injection, the gel comprising 5-50 parts of silk fibroin, 0.01-5 parts of cellulose, and 0.7-10 parts of hyaluronate, and the gel is prepared according to the following steps: (1) Preparation of silk fibroin microfiber gel: adding cellulose to a silk fibroin aqueous solution to prepare a gel, crushing it, and sieving it to obtain a silk fibroin microfiber gel; (2) Preparation of extracellular skeleton gel material: Hyaluronate is mixed with silk fibroin microfiber gel to make them physically cross-linked to form a silk fibroin extracellular skeleton gel material; The gel material does not include any chemical cross-linking agents.
2. The material according to claim 1, characterized in that The molecular weight of the silk fibroin is between 50 kDa and 350 kDa; the silk fibroin aqueous solution is prepared by dissolving and purifying degummed silk of mulberry silk or tussah silk.
3. The material according to claim 1, characterized in that The cellulose is hydroxyl-containing cellulose, further one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and hydroxyethyl cellulose, more preferably hydroxypropyl methyl cellulose and hydroxypropyl cellulose, and most preferably hydroxypropyl methyl cellulose.
4. The material according to claim 1, characterized in that The molecular weight of the hyaluronate is between 500 kDa and 2400 kDa, preferably in the range of 1500 kDa-2400 kDa; The hyaluronate solution is prepared from a sodium hydroxide aqueous solution with a mass concentration of 0.1% to 1% of hyaluronate.
5. The material according to claim 1, characterized in that: After the gel material is prepared, it is purified by dialysis, and the dialysate is one of an isotonic phosphate buffer solution or a PBS buffer solution.
6. The material according to any one of claims 1 to 5, characterized in that: Silk fibroin: hyaluronate is greater than or equal to 2:1, 3:1 or 4:
1.
7. The material according to any one of claims 1 to 6, characterized in that: The gel is composed of 5-50 parts of silk fibroin, 0.01-5 parts of cellulose, and 0.7-10 parts of hyaluronate, preferably 10-50 parts of silk fibroin, 0.01-5 parts of cellulose, and 0.7-5 parts of hyaluronate.
8. The method for preparing the material according to claim 1, characterized in that: (1) Preparation of silk fibroin microfiber gel: adding cellulose to a silk fibroin aqueous solution to prepare a gel, crushing it, and sieving it to obtain a silk fibroin microfiber gel; (2) Preparation of extracellular skeleton gel material: Hyaluronate is mixed with silk fibroin microfiber gel to make them physically cross-linked to form a silk fibroin extracellular skeleton gel material.
9. The preparation method according to claim 8, characterized in that: (1) Put the silk of mulberry silk into a boiling sodium carbonate aqueous solution with a mass fraction of 0.1-5% or a mixed solution of sodium carbonate and sodium bicarbonate, heat and boil for 10-120 minutes, dry at 25-100°C, dissolve in a 9.3 mol / L lithium bromide aqueous solution, and place in a water bath at 25-100°C for 10-120 minutes until the silk protein is fully dissolved, filter out insoluble particulate impurities with a 50-200 mesh filter bag, and obtain a silk protein aqueous solution with a specific molecular weight after desalting and concentration; add the silk protein solution with a mass concentration of 20% to the cellulose solution, and then ultrasonically treat it with an ultrasonic crusher; after gelation, homogenize it at 1500-24000 rpm / min for 5 minutes, sieve, and collect the silk protein microfiber gel passing through a 200-325 mesh sieve; (2) Preparation of extracellular skeleton gel: prepare hyaluronic acid particles, mix with silk fibroin microfiber gel, let stand for 2 to 12 hours at 25 to 60°C to allow physical cross-linking, dialyze with dialysate, fill, and sterilize to form a silk fibroin extracellular skeleton gel material.
10. A use of the controllable silk fibroin extracellular skeleton gel material for injection according to any one of claims 1 to 7, characterized in that: Used for cosmetic fillers or medical fillers.
11. The use as claimed in claim 10, for filling and repairing skin tissue or soft tissue, which can promote in situ tissue regeneration, especially for face, trunk or limbs.
Citation Information
Patent Citations
Silk fibroin / cellulose 3D printing ink
CN106267370A
Silk fibroin hydrogel
CN108404204A
Method of preparing silk fibroin-tyramine modified hyaluronic acid hydrogel material based on physical-chemical cross-linking
CN110172163A
Cross-linked hyaluronic acid or hyaluronic acid salt gel with interpenetrating network structure and preparation method of cross-linked hyaluronic acid or hyaluronic acid salt gel
CN115612184A
Injectable silk protein microsphere gel with adjustable performance and preparation method of injectable silk protein microsphere gel
CN115671388A
Cited By
Preparation method of soluble regenerated silk fibroin freeze-dried powder with controllable molecular weight
CN120842350A
A method for preparing a soluble regenerated silk fibroin freeze-dried powder with controllable molecular weight
CN120842350B
Silk fibroin freeze-dried powder as well as preparation method and application thereof
CN120966087A
Controllable fibroin extracellular scaffold gel material for injection and method for preparing same
WO2026008079A1